VD_FINDINFO HC / 2009 / 325 vom 22. September 2009 - VD Tribunal cantonal (2009)
HARCÈLEMENT PSYCHOLOGIQUE, RÉSILIATION, RÉSILIATION ABUSIVE, FARDEAU DE LA PREUVE, PREUVE | 321a al. 1 CO, 321a CO, 328 al. 1 CO, 328 CO, 336b al. 1 CO, 336b CO